1999
DOI: 10.1115/1.2833937
|View full text |Cite
|
Sign up to set email alerts
|

CFD Comparison to 3D Laser Anemometer and Rotordynamic Force Measurements for Grooved Liquid Annular Seals

Abstract: A pressure-based computational fluid dynamics (CFD) code is employed to calculate the flow field and rotordynamic forces in a whirling, grooved liquid annular seal. To validate the capabilities of the CFD code for this class of problems, comparisons of basic fluid dynamic parameters are made to three-dimensional laser Doppler anemometer (LDA) measurements for a spinning, centered grooved seal. Predictions are made using both a standard and low Reynolds number κ-ε turbulence model. Comparisons show good overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…S k and S ε are user-defined source terms [12]. The capability of the κ-ε turbulence model for the grooved liquid annular seal has been validated by comparison between the computed results and the threedimensional laser Doppler anemometer measurements [13].…”
Section: Computational Descriptionsmentioning
confidence: 99%
“…S k and S ε are user-defined source terms [12]. The capability of the κ-ε turbulence model for the grooved liquid annular seal has been validated by comparison between the computed results and the threedimensional laser Doppler anemometer measurements [13].…”
Section: Computational Descriptionsmentioning
confidence: 99%
“…Soviet scholars studied the spiral effect of aerodynamic flow in a high-pressure turbine rotor and found that the inertial effect of aerodynamic flow is far greater than the friction effect in the sealing gap [15]. At the end of the twentieth century, more researchers began to study aerodynamic excitation forces and the interaction forces between impeller and flow section [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Attention has been given to fluidinduced force for the improvement of turbine operating parameters. In the past years, many studies [1][2][3][4][5][6] used CFD techniques to simulate the flow behavior in seals. Many factors, such as turbulent flow, boundary condition, and temperature variation, among others, cannot be considered accurately.…”
Section: Introductionmentioning
confidence: 99%